Industrial Restructuring in East Asia Towards the 21st Century - Masuyama, Seiichi; Siow Yue, Chia; Vandenbrink, Donna (ISEAS Publishing, 2001)
This book is about the restructuring of industry in ten East Asian economies at the start of the twenty-first century. It examines the dynamic aspects of the region's industrial structures -- the changes occurring with globalisation fuelled by liberalisation and by a paradigm shift from industrial technology to information technology. The traditional "flying geese" concept is less relevant to explaining the economic and industrial development in the region as the pattern has become less predictable